Double aortic dissection in a patient with Marfan disease. A case report - Rosa Christian, Millogo Georges; Koudougou, Kologo Jonas; André Arthur, Seghda Taryètba; Théodore, Boro; Laurence, Benon; K, Samadoulougou André; Patrice, Zabsonré (Journal of Cardiology and Cardiovascular Medicine, 2022)
Marfan syndrome is a dominant autosomal genetic disease of the connective tissue, leading to various complications. Cardiovascular complications are the main ones, with dilation of the aorta and aortic dissection which is the main cause of death. Double dissection with different sites of departure is scarcely reported by the literature. We reported the case of a 22-year’s-old young patient admitted for acute chest and abdominal pains, and cardiogenic shock. Investigations reported a double dissection of the aorta with a recent one of type A and an old one of type B. Ghent diagnostic criteria were used to allow the diagnosis of Marfan disease. Surgical management corrected successfully the type A dissection. Early diagnostic and adequate management of aortic complications can reduce the high mortality rate of patients with Marfan syndrome.